Cortisol fetal fluids concentrations and newborn outcome in term pregnancy small-sized purebred dogs. (International Journal of Health, Animal Science and Food Safety, 2016)
In order to provide further information about canine perinatology, and because of the scarceknowledge about fetal fluids composition in dogs, the present study was aimed to assess the cortisolconcentrations in fetal fluids collected from small-sized purebred newborn puppies born by electivecesarean section, at term of pregnancy (Meloni et al, 2014). Furthermore weassessed possible correlations of amniotic and allantoic cortisol concentrations and newborn outcomeat 24 hours of age and with the newborn gender. Fetal fluids cortisol concentrations were alsoevaluated for correlation with maternal parity, litter-size, neonatal gender, birth weight and Apgar score(Veronesi et al, 2009). The study, performed on 50 born alive, normal weighed puppies, without grossphysical malformation, showed that cortisol concentration was higher in allantoic than in amniotic fluid(p
Keywords: Term pregnancy; fetal fluids; cortisol; newborn outcome